Case Report: From epilepsy and uterus didelphys to Turner syndrome-associated dysgerminoma - Li, Jinghua; Zhu, Haipeng; Ma, Xuelian; Li, Jia; Xue, Jing; Feng, Limin (Frontiers in Genetics, 2024)
Dysgerminoma is a rare occurrence in Turner syndrome patients without Y chromosome mosaicism or hormone therapy during puberty. We present a unique case of a 33-year-old nulliparous Chinese female with intermittent epilepsy and Mullerian anomalies carrying a double uterus, cervix and vagina. The patient is also characterized as Turner syndrome accompanied by 46,X,) and del(2)(q11.1-11.2).An MRI exhibited a 17.0x20.0x10.5cm solid ovarian lesion. Radical surgery and pathology revealed dysgerminoma at stage IIIc with lymphatic metastases and a KIT gene mutation identified in exon 13. Furthermore, the tumor microenvironment displayed robust expression of CD4 + T lymphocytes and PD-1, whereas distribution of CD8 + T lymphocytes and PDL-1 is sporadic. Despite enoxaparin used to prevent thromboembolism, the patient experienced multiple cerebral infarctions during chemotherapy. Subsequently, the patient declined further treatment and was discharged. This exceptional case imparts several noteworthy lessons. Firstly, the coexistence of Mullerian anomalies, though rare, is not incompatible with Turner syndrome. Secondly, screening for KIT mutations is imperative to reduce the risk of dysgerminoma in Turner syndrome, especially for patients with Y mosaicism who are preparing for hormone replacement therapy. Lastly, comprehensive anticoagulation therapy is crucial for Turner syndrome patient undergoing cisplatin-based chemotherapy.